Culture-Negative Endocarditis in an Immunocompromised Patient: A Case of Suspected and Co-Infection - Steven Swarath MBBS; Nicole Maharaj MBBS; Tiffany Kawall MBBS; Rajeev Seecheran MBBS, MHA; Valmiki Seecheran MBBS, MSc; Stanley Giddings MBBS; Naveen Anand Seecheran MBBS (MD) (SAGE Publishing, 2023)
We present the case of a 23-year-old man with a previous deceased-donor renal transplant maintained on tacrolimus and prednisone who developed culture-negative endocarditis (CNE) of the mitral and aortic valves. He was suspected of being co-infected with Bartonella henselae and Coxiella burnetii , confirmed with serology testing. He was successfully managed with appropriate antibiotics and dual valve replacement.